Redesign of the user interface for the career development center (CDC) website, Telkom University Bandung - Ahmad Aqil Muntaz; I Dewa Alit Dwija Putra; Ananda Risya Triani (Jurnal Desain, 2025)
Nowadays, the development of the job market is becoming increasingly competitive. Companies have various specific criteria for their prospective employees. In addition to having a degree, job candidates are also required to possess various soft skills. Therefore, Telkom University, through the Career Development Center (CDC), strives to prepare its students for employability. The Career Development Center (CDC) at Telkom University operates a website that serves as a digital platform for information sharing and interaction with both students and alumni. However, based on the results of the observation, issues were found on the website, including a user interface that is considered neither informative nor visually appealing. Considering the main function of this website is as a center for information and interaction among the academic community, a redesign of the CDC Telkom University website is necessary using a design thinking approach as the design method. Data was collected through observation and interviews, which were then analyzed using descriptive analysis methods to produce a user interface design that meets user needs. The result of this design process produced a new CDC website design in the form of a high-fidelity prototype that has undergone testing using the usability testing method and received positive feedback from end users. Through the redesign of this website's user interface, it is hoped that a good user experience will be achieved, allowing the Career Development Center of Telkom University to optimally convey information.